2021
DOI: 10.3390/s21155108
|View full text |Cite
|
Sign up to set email alerts
|

A Preference-Driven Smart Home Service for the Elderly’s Biophilic Experience

Abstract: Smart home services (SHS) should support the positive experiences of the elderly in homes with a focus on getting closer to nature. The study identified the services preferred by the elderly through a survey on the biophilic experience-based SHS, and to discuss the configuration of the sensors and devices required to provide the service. We reorganized the biophilic experience-based SHS and related sensors and devices, focusing on our previous study, and developed a survey instrument. A preference survey was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…While the effect of architecture and interior design on human health and productivity has been extensively explored in places like hospitals and primary schools, more research is needed on the impact of biopsychosocial and biophilic design in urban higher education institutions [30]. Implementing health-promoting and restorative environmental design solutions may help university students overcome IOP Publishing doi:10.1088/1755-1315/1218/1/012020 4 some of the particular issues they experience and positively impact their lives and education.…”
Section: Influence Of Biophilic Design On Psychological Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…While the effect of architecture and interior design on human health and productivity has been extensively explored in places like hospitals and primary schools, more research is needed on the impact of biopsychosocial and biophilic design in urban higher education institutions [30]. Implementing health-promoting and restorative environmental design solutions may help university students overcome IOP Publishing doi:10.1088/1755-1315/1218/1/012020 4 some of the particular issues they experience and positively impact their lives and education.…”
Section: Influence Of Biophilic Design On Psychological Well-beingmentioning
confidence: 99%
“…Emotional stress, happiness, stimulation, cognitive function, social support, belonging, study spaces, lighting, and ventilation are all identified as important topics in the published multi-disciplinary research about the built environment's impact on university students [12]. The semi-structured literature review identifies, evaluates, and categorizes important research on nature views, nature pictures, natural colors, natural materials, auditory and olfactory components of nature, nature images with water, indoor plants, campus landscapes, study spaces, local materials, and style, daylight access, thermal and environmental comfort [30]. While it is common knowledge that exposure to nature may positively affect health and productivity, further research is required to determine the optimal greenery dosage and its associated well-being advantages for use in design practice.…”
Section: Influence Of Biophilic Design On Psychological Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…As the efficient development of space using digital technology is being promoted, related studies are discussing biophilic experiences using immersive technologies, robotics, and Natural Language Understanding (NLU) [ 5 , 33 , 70 , 71 ]. Particularly, in the field of environmental psychology, VR and AR are being used to effectively control experimental environments and variables, and to quantify human responses to them.…”
Section: Related Workmentioning
confidence: 99%
“…Immersive technologies such as VR and AR enable the simulation of virtual natural environments and elements, the investigation of biological responses according to conditions [ 9 , 12 , 72 ], and a comparison with the real environment [ 73 , 74 ]; as a result these technologies have resulted in new approaches to biophilic design research. Other studies using NLU, which have contributed to the extended scope of biophilic experiences, also deal with direct and indirect interactions with virtual natural elements through facial expressions, behaviors, and psychological states [ 70 , 75 ], and investigate emotional and cognitive responses of social care robots similar to real companion animals [ 76 , 77 ]. The results of this study proved that an experience with nature mediated by digital technology and virtual elements also had a profound effect on human health and quality of life, suggesting the possibility of hybridization of biophilic experiences.…”
Section: Related Workmentioning
confidence: 99%